MASALAH BELAJAR PESERTA DIDIK YANG TIDAK TINGGAL DENGAN ORANG TUA (Suatu Kajian di SMA Negeri 1 Rao Kabupaten Pasaman) - Rina, Silvia - (Bimbingan dan Konseling, 2014)
This research was influenced by learningâs problem of the students who does not live with their parents. Based the result of the observation that the learningâs problem is still found such as; the students unconcerned and could not be concentrated on the teaching- teaching learning process. This research aim was to determine the students learning problems. The kind of this research is descriptive-quantitative research. The population is the entire student who does not live with their parents in 54 students. The sampling was totaling sampling technique. The instrument was used questionnaire to data collection and formulation of % to data analysis. The result of this research was found; (1) The hit category in internal factor, (2) The minimal category in external factor. In generally, the students do not have problem in the learning despite does not live with their parents and there are some problems in learning students too.